The Influence of the Effectiveness on Physical Activity in Patients with COPD Symptom Burdens - Aini, Hafizatul; Yulia, Yulia (Indonesian Journal of Global Health Research, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is characterized by prolonged airflow limitation with a high symptom burden that interferes with physical activity and results in inactivity and worsens the sufferer's condition. Objective: This study aims to determine the effectiveness of physical activity on the symptom burden that affects patients with Chronic Obstructive Pulmonary Disease (COPD). Method: The method used in writing this article is a literature review using three databases PubMed, ScienceDirect and Taylor and Francis Online with the keywords symptom burden, physical activity, COPD and quality of life. The articles published range from 2020 to 2024. During the search stage, 115 articles were found and 8 articles were found that met the criteria for review. Result: The results of the article review show that physical activities carried out by COPD sufferers such as walking, doing aerobic exercise, breathing exercises, Tai Chi movements, daily activities at home (Activity Daily Living/ADL) can be adjusted to the condition, duration, intensity and can be measured through assessments. patterns of physical activity levels (PALs), using pedometers and accelerometers. Physical activity is carried out based on guidance from health workers, physical activity counseling and home exercise (HE) effectively, easily and at a cheaper cost. Conclusions: The conclusion is that physical activity can be carried out in mild to severe COPD sufferers to maintain the activity of COPD patients in the long term and overcome symptom burden, improve lung functional status, improve general health status and improve the quality of life of COPD patients.